Evaluation of Tissue Tropism and Horizontal Transmission of a Duck Enteritis Virus Vectored Vaccine in One-Day-Old Chicken - Yassin Abdulrahim; Yingying You; Linggou Wang; Zhixiang Bi; Lihua Xie; Saisai Chen; Benedikt B. Kaufer; Armando Mario Damiani; Kehe Huang; Jichun Wang (Viruses)
Herpesvirus of turkey (HVT) recombinant vector vaccines are widely used in the poultry industry. However, due to limitations in loading multiple foreign antigens into a single HVT vector, other viral vectors are urgently needed. Since chickens lack maternal immunity to duck enteritis virus (DEV), vector vaccines using DEV as a backbone are currently under study. Even though a recently developed DEV vector vaccine expressing the influenza hemagglutinin H5 of highly pathogenic avian influenza (DEV-H5) induces highly detectable anti-HA antibodies, safety issues hamper further vaccine development. In this work, tissue affinity and horizontal transmission in 1-day-old chickens were systematically evaluated after DEV-H5 vector vaccine inoculation. Sixty percent of DEV-H5-inoculated chickens died between day 2 and day 7 post-inoculation. The displayed clinical signs consisted of lethargy, anorexia, and diarrhea, and virus was shed in feces. Gross and/or histological lesions were recorded in the kidney, heart, intestine, liver, lung, and spleen. Moreover, DEV-H5 replication in intestinal cells caused an increment in interferon-α expression, while occluding junction proteins and ZO-1 expression were significantly upregulated. As a control, birds inoculated with a commercial recombinant turkey herpesvirus expressing the VP2 protein of the infectious bursal disease virus (HVT-VP2) vector vaccine showed neither clinical signs nor mortality. Overall, while the HVT-VP2 vaccine demonstrated complete safety in 1-day-old chickens, our potential DEV-H5 vaccine requires further attenuation for consideration as a vector vaccine candidate in chickens.